PERUSAHAAN JASA PENGURUSAN TRANSPORTASI (PJPT) SEBAGAI "PENGANGKUT" KAITANNYA DENGAN PERLINDUNGAN HUKUM DAN PEMBAHARUAN DALAM RANGKA PEMBANGUNAN HUKUM PENGANGKUTAN NASIONAL - Dyah Ersita Yustanti (JURNAL HUKUM STAATRECHTS, 2018)
AbstractCarriage of goods activities is needed in the mobilization of goods and services for Indonesia which consists of archipelagic country, so the business activities of expeditor plays an important role. The expeditor which is nowadays known as Freight Forwarding Company (Perusahaan Jasa Pengurusan Transportasi (PJPT)) pursuant to Article 86 of the Indonesian Commercial Code was the agent and now has experiencing development, as it is become the "carrier". This development brings impacts to the responsibility so that it was obtained 2 (two) main issues: (1) Why is it necessary to develop a law for the protection of PJPT in its capacity as a "carrier", and (2) How is the responsibility of PJPT as a "carrier" for the possibility of risk of loss?. From the result of the research, it can be concluded that: (1) the Government has made the regulation concerning the obligation to insure the responsibility of PJPT but has not been implemented by PJPT and (2): In the Indonesian Commercial Code, the expeditor is the agent and the bill of lading issued by the carrier, but the Ministerial Regulation defines PJPT as "carrier" because it can issue a bill of lading so that PJPT becomes a principal, also that the Ministerial Regulation enforces the international customs and regulations in the carriage of goods in Indonesian. Keyword: PJPT,  Legal Protection, Development Law